What biomechanical parameters are related to drag-flick performance in field hockey? A systematic review - Ladru, B.-J.; Beddows, T.; Langhout, R.; Gijssel, M.; Tak, I. (Sports Biomechanics, 2023)
The drag-flick is a highly relevant skill to enlarge scoring opportunities during penalty corners in field hockey. Understanding drag-flick biomechanics will likely assist in optimising training and performance of drag-flickers. The purpose of this study was to identify the biomechanical parameters related to drag-flicking performance. Five electronic databases were systematically searched from inception to 10 February 2022. Studies were included if quantified biomechanical parameters of the drag-flick were assessed and related to performance outcomes. Quality assessment of the studies was performed according to the Joanna Briggs Institute critical appraisal checklist. Study type, study design, participants` characteristics, biomechanical parameters, measurement instrumentation and results were extracted from all included studies. The search yielded 16 eligible studies (142 drag-flickers). Many different single kinematic parameters were associated with drag-flick performance and related to biomechanical aspects described in this study. Nonetheless, this review identified a lack of a solid body of knowledge on this topic due to a low number of studies as well as low study quality and strength of evidence. Future high-quality research is needed to develop a clear biomechanical blueprint of the drag-flick to better understand this complex motor skill.